Translation facilitates comprehension of health-related crisis information: Kenya as an example - Sharon O'Brien; Patrick Cadwell (JoSTrans: The Journal of Specialised Translation)
This paper examines the relationship between translation and comprehension when communicating health-related information during a crisis. It tests comprehension levels among a population of rural and urban Kenyans of health-related crisis communication presented to them in an English source text and a Kiswahili target text. These data were gathered in Kenya in collaboration with a non-profit organisation, Translators without Borders, and the overarching aim of the project was to assess empirically the potential impact of translation on comprehension of health-crisis content. Findings indicate that English is not a suitable medium for the transfer of important health-related information among the cohort of participants in this study, despite English being an official language of Kenya. In contrast, Kiswahili, also an official language, seems to function well. As a result, a need for translation into Kiswahili in this context has been empirically shown. It was further found that written modes of communication are not necessarily the most appropriate modes for the dissemination of health-related crisis information among this cohort. This presents interesting challenges for governments, crisis response agencies, and translators alike, and these challenges are discussed.